A p.P30L Mutation at the CYP21A2 Gene in Macedonian Patients with Nonclassical Congenital Adrenal Hyperplasia - Anastasovska, V; Kocova, E; Kocova, M (Walter de Gruyter GmbH, 2010)
A p.P30L Mutation at the CYP21A2 Gene in Macedonian Patients with Nonclassical Congenital Adrenal HyperplasiaNonclassical congenital adrenal hyperplasia (NCAH) is an autosomal recessive imbalance in cortisol synthesis with adrenal androgen excess. Although rarely recognized in infants, it may cause premature adrenarche and pubarche, virilization in young women and variable symptoms in young men. It is commonly caused by mutations in CYP21A2, the gene for steroid 21-hydroxylase. Patients with the p.P30L allele tend to have pronounced evidence of androgen excess but are categorized as nonclassical. We used direct molecular detection of the p.P30L mutation in CYP21A2 in 11 Macedonian NCAH patients and in 17 members of their families using polymerase chain reaction/amplification created restriction site (PCR/ACRS) analysis and digestion with restriction enzymes. The p.P30L mutation was found in a homozygous state in seven (63.6%) and in a heterozygous state in four (36.4%) patients. Of the latter, one was also heterozygous for the p.Q318X mutation. The p.P30L mutation was found in a heterozygous state in 10 (58.8%) and in a homozygous state in one (5.9%) of the family members. These findings support a role of the p.P30L mutation in NCAH.